Pawnshops Regulatory Environment: A Readability Analysis - Geralyn Miller; Steven A. Hanke; Hui Di (Journal of Accounting, Business and Management (JABM), 2018)
The pawn industry in the United States grew substantially in recent years; however, there is limited research on the regulatory environment for these predominately small businesses. Our study focuses on the readability of state regulations for pawnshops. We select credit unions as a comparison group since they also service non-bank customers. Our analysis reveals that the majority of states’ pawnbroker regulations are at the college reading level while the regulations for credit unions are at the college graduate reading level. There are also geographical differences in the readability of pawnshop regulations with the regulations in the northeast region being easier to read than in the west region. However, there is no evidence that the regulations readability level corresponds to the number of pawnbrokers in a state or to more broad-based measures of state-level business friendliness.